2nd generation bioethanol production in terms of circular economy - Branco, Rita Henriques Rebola (2020)
Circular Economy (CE) is a promising solution for the unsustainable material and energy flow model of the current economic system. Biorefineries are crucial for CE as they process all fractions of biomass to co-produce a multiplicity of products and energy, minimizing waste generation. Bioethanol, with lower greenhouse gasses emissions, is a potential alternative to fossil fuels, which have negative impacts in health and environment. Bioethanol is currently the most produced biofuel and is almost entirely of first generation since it is produced from food crops, leading to food-fuel competition. In alternative, second generation bioethanol is produced from lignocellulosic biomass (LCB) but requires a costly and technically difficult pretreatment. In pulp and paper industry the Kraft pulping step removes lignin and targets hemicelluloses, releasing cellulose, and therefore can be considered as a pretreatment of LCB. A process based on Kraft pulping followed by the hydrolysis of polysaccharides and subsequent fermentation emerges as a promising approach to valorise wastes resulting from pulp and paper industry, converting the existing mills in integrated biorefineries. The aim of this work was to study the production of bioethanol using yeast Saccharomyces cerevisiae and Scheffersomyces stipitis from unbleached Kraft pulp of Eucalyptus globulus, exploiting the Kraft pulping process as LCB pretreatment. Enzymatic hydrolysis of unbleached Kraft pulp of E. globulus released hydrolysates with 65.4 ± 0.8 g.L-1 of glucose and 16.0 ± 1.8 g.L-1 of xylose, corresponding to a yield of 95.6 ± 2.6 %. In Erlenmeyer flask assays, S. cerevisiae yeast showed higher ethanol concentration, 19.81 ± 0.15 g.L-1, ethanol yield, 0.450 ± 0.009 g.g-1, and ethanol productivity, 2.01 ± 0.01 g.L-1.h-1, than Scheffersomyces stipitis. Neither S. cerevisiae and S. stipitis sequential co-culture nor simultaneous co-culture showed a significant improvement in these parameters compared with S. cerevisiae mono-culture. S. cerevisiae mono-culture fermentation of Kraft pulp hydrolysate in bioreactor resulted in an ethanol concentration of 19.24 g.L-1, an ethanol yield of 0.433 g.g-1, and an ethanol productivity of 0.733 g.L-1.h-1. Also, in bioreactor, sequential co-culture did not show any improvement from S. cerevisiae mono-culture. The high ethanol yield and productivity obtained by S. cerevisiae mono-culture fermentation of E. globulus Kraft pulp hydrolysate show that this is a promising process for second generation bioethanol production. Also, given these results, it appears that producing bioethanol from pulp and paper industry wastes, such as low-quality wood, bark, and other rejects, as well as low-quality and excess pulp, is a potential opportunity for implementing integrated biorefineries in the existing Kraft pulp mills.